POTENSI JIWA WIRASWASTA MASYARAKAT DESA TERTINGGAL DI DIY - Farida Hanum (Jurnal Penelitian Humaniora, 2002)
Abstract This study is intended to find the potential of the entrepreneur spirit of the underdeveloped villagers in DIY and its relationship with their resources. How far is the potential able to be developed? This study was done in four regencies are Sleman, Bantul, KulonProgo and Gunungkidul regency. The population of this research is the member of the underdeveloped villager who is 17 to 55 years old and who has already had a job. The total number of this research’s sample is 155 people. The data was taken from the questionnaires distributed.  Besides, to complete this research’s data, I held interview to the key figure of the society. Using cross tab analysis technique of SPSS computer program/PCT processed the data. The result got shows that the entrepreneur spirit of the DIY’s an underdeveloped villager is in range. So it can be said that the entrepreneur spirit’s potential of the villagers can be increased by using programs that support the entrepreneur’s attitude. The formal-education background does not directly support the increase of the entrepreneur spirit. Yet, the non-formal education background might have big role in it. The people of the age 20-29 are the group of the villagers who has big entrepreneur spirit. Commonly, those people work as employer of factories and traditional industries. Keywords: potential, entrepreneur spirit, and underdeveloped village.